School leadership, school inspection and the micropolitics of compliance and resistance: Examining the hyper-enactment of policy in an area of deprivation. (March 2021) - Colman, Aly
This paper examines the influence of intense scrutiny from Ofsted on school leadership and policy enactment. Data was collected in a coastal area of deprivation, providing the setting for a detailed case study of school leadership in a state secondary school and a state primary school, both with recent or ongoing experience of intense scrutiny from Ofsted. Seventeen interviews were undertaken with staff involved in leadership roles. The analyses of data and discussion form an understanding of how policy is enacted in relation to the dual responsibility that school leaders negotiate between the local context at Seatown and Ofsted. This paper suggests that Ofsted forces a privileging of a compliant and consistent enactment of policy; a hyper-enactment of policy, that reduces the capacity of school leaders to address the significant social context of the school. Foucault's work on self-disciplinary technologies provides insight into the micropolitical spaces which open up for some school leaders. The discussion on the micropolitics of compliance and resistance offers insight into the tensions pertinent to school leadership teams and explores issues relevant to those interested in policy and inspection activity, particularly those within areas of deprivation.